Static performance of steel temcor joints subjected to axial tension and compression loads. (January 2023) - Mashrah, W.A.H.; Chen, Zhihua; Liu, Hongbo; Rima, Boufendassa; Mogalli, Abdullah
Abstract: In this study, steel temcor joints with Huck bolts (10.9 grade) for single-layer grid-shell structures were investigated. Experimental, numerical, and theoretical methods were adopted to explore the behaviour of the temcor joint of steel under axial tension and compression loads. In the beginning, six specimens with a single Huck bolt were designed to investigate the failure mode and the shear strength of the Huck bolt. And then, steel temcor joints (TC1, TC2, and TC3) were designed and tested considering the number of Huck bolts and the gusset plate thickness. In the test, the TC1 joint with only eight Huck bolts exhibited the lowest load-bearing capacity with main bolt shear failure under tension and compression loads. Moreover, the TC2 and TC3 joints exhibited higher bearing capacities with bolt shear failure in the tension tests, while they generated the same compressive bearing capacities with the main failure occurring in the H-shaped beam. A 1/6 FE models for three types of specimens in the tension and compression tests were established using Abaqus software. Simultaneously, a parametric analysis was conducted to explore the impact of the gusset plate thickness on the performance of steel temcor joints. The tension and compression theoretical solutions were derived. Finally, the steel temcor joint with Huck bolt exhibited excellent stiffness and bearing capacity which can satisfy the design requirements for the single-layer grid shell structures.